Lysophosphatidylcholine Promotes Phagosome Maturation and Regulates Inflammatory Mediator Production Through the Protein Kinase A–Phosphatidylinositol 3 Kinase–p38 Mitogen-Activated Protein Kinase Signaling Pathway During Mycobacterium tuberculosis Infection in Mouse Macrophages - Lee, Hyo-Ji; Ko, Hyun-Jeong; Song, Dong-Kun; Jung, Yu-Jin (Frontiers in Immunology, 2018)
Tuberculosis (TB) is caused by the infectious agent Mycobacterium tuberculosis (Mtb). Mtb has various survival strategies, including blockade of phagosome maturation and inhibition of antigen presentation. Lysophosphatidylcholine (LPC) is a major phospholipid component of oxidized low-density lipoprotein and is involved in various cellular responses, such as activation of second messengers and bactericidal activity in neutrophils. In this study, macrophages were infected with a low infectious dose of Mtb and treated with LPC to investigate the bactericidal activity of LPC against Mtb. In macrophages infected with Mtb strain, H37Ra or H37Rv, LPC suppressed bacterial growth; however, this effect was suppressed in bone marrow-derived macrophages (BMDMs) isolated from G2A (a G-protein coupled receptor involved in some LPC actions) knockout mice. LPC also promoted phagosome maturation via PI3K-p38 MAPK-mediated ROS production and intracellular Ca2+ release during Mtb infection. In addition, LPC induced increased levels of intracellular cAMP and phosphorylated GSK3β in Mtb-infected macrophages. PKA-induced phosphorylation of GSK3β suppressed activation of NF-κB in LPC-treated macrophages during Mtb infection, leading to decreased secretion of pro-inflammatory cytokines and increased secretion of anti-inflammatory cytokines. These results suggest that LPC can effectively control Mtb growth by promoting phagosome maturation via cAMP-induced activation of the PKA-PI3K-p38 MAPK pathway. Moreover, LPC can regulate excessive production of pro-inflammatory cytokines associated with bacterial infection of macrophages.